2019
DOI: 10.1002/jbio.201800260
|View full text |Cite
|
Sign up to set email alerts
|

Weak biophoton emission after laser surgery application in soft tissues: Analysis of the optical features

Abstract: Nowadays, laser scalpels are commonly used in surgery, replacing the traditional surgical scalpels for several applications involving cutting or ablating living biological tissue. Laser scalpels are generally used to concentrate light energy in a very small‐sized area; light energy is then converted in heat by the tissues. In other cases, the fiber glass tip of the laser scalpel is heated to high temperature and used to cut the tissues. Depending on the temperature reached in the irradiated area, different eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…We previously reported that high‐intensity focused ultrasound or direct heating leads to a weak light emission from soft tissues [25]. Moreover, we verified that in laser‐induced artificial lesions on soft tissues the light emission is due to heat rather than to light stimulation [20]. Thus, it is reliable that light emission is generated by heat also in the bone.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We previously reported that high‐intensity focused ultrasound or direct heating leads to a weak light emission from soft tissues [25]. Moreover, we verified that in laser‐induced artificial lesions on soft tissues the light emission is due to heat rather than to light stimulation [20]. Thus, it is reliable that light emission is generated by heat also in the bone.…”
Section: Discussionsupporting
confidence: 65%
“…Using an 810 nm diode laser on the oral mucosa of fresh pig mandibles, Goharkhay et al observed that the depth of the epithelial damage depended on laser penetration and correlated strongly with average powers used [19]. Recently, we demonstrated that a surgical diode laser operating at 808 nm with power in 3 to 9 W range is suitable to evaluate thermoluminescence emission from soft tissues [20]. Using the same laser, in this study we aim at elucidating the thermo‐optical features of laser‐irradiated bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These results also suggest us that surgery and CLI should not be performed much later than 4 h after injection, in order for CLI to able to detect surgical margins. Another possible complication is light emission by soft tissues due to the laser excision of the specimen [15]. This phenomenon has been observed both in the breast and in the prostate, thus we expect a similar behavior also for the liver.…”
Section: Discussionmentioning
confidence: 56%
“…The higher the level of an organism is, the greater intensity of the photon radiation that is emitted. The research applying of biophoton technology has been mainly conducted in medical fields, such as medical information diagnosis [11], cancer classification [12], analysis of brain activities [13], and others. In the cereal storage field, however, biophoton studies mainly focus on insect intrusion rather than on wheat mould.…”
Section: Fig 1 Global Consumption Of Wheat and Year-on-year Percentmentioning
confidence: 99%